Sistema didático para controle de máquinas elétricas em laboratórios de ensino e pesquisa - Andrade, Allan Vinícius de Sousa (2019)
[EN] Currently, several solutions for the Control of Electric Machines in a teaching and research environment are already available in the market. However, these solutions often run counter to limited budgets, representing a high investment for most universities. The present work aims at the development of an integrated solution, low cost, directed to the study of the Control of Electric Machines. The basis of the hardware is a DSC, which guarantees the power of data processing in real time. The basis of the software is offered by the Simulink / Matlab program, which offers ease of programming compared to direct DSC programming. This provides a more economical and user-friendly solution that can be adopted on a large scale in academic environments for future projects.